1981
DOI: 10.1007/bf00257787
|View full text |Cite
|
Sign up to set email alerts
|

Insulin degradation. XXVIII. Immunocytochemical localization of glutathione-insulin transhydrogenase in the pancreas, kidney and liver of normal and streptozotocin-diabetic rats and of lean and obese (ob/ob) mice

Abstract: Glutathione-insulin transhydrogenase catalyzed the inactivation of insulin by splitting the hormone into A and B chains. We have localized this enzyme immunocytochemically by light microscopy in the pancreas, kidney and liver of both lean and obese (ob/ob) mice and similarly in normal and streptozotocin-diabetic rats. Localization was achieved by an antibody to glutathione-insulin transhydrogenase using a peroxidase-antiperoxidase technique. In comparison with tissues from control animals, positive immunostain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A previous study [27] also reported few surviving disorganized islets with marked destruction of β cells in STZ-induced diabetic rats. A previous study [27] also reported few surviving disorganized islets with marked destruction of β cells in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 68%
“…A previous study [27] also reported few surviving disorganized islets with marked destruction of β cells in STZ-induced diabetic rats. A previous study [27] also reported few surviving disorganized islets with marked destruction of β cells in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 68%
“…When a supraphysiological concentration of insulin is used as substrate, GIT may be the most active of all insulin-degrading enzymes in the kidney, although GIT activity may be lower than normal in the kidneys of animals with chemically-induced diabetes. GIT, which is localized to the proximal tubule [61], reduces the disulphide bonds of insulin, producing separate, but intact, A and B chains, which can be degraded rapidly by the non-specific peptidases which are present in intracellular organelles [60], especially lysosomes. Together, GIT and lysosomal proteases could catalyze the initial, specific and later, non-specific steps, respectively, of insulin degradation by proximal tubular cells.…”
Section: Enzymatic Mechanisms Of Renal Insulin Degradationmentioning
confidence: 99%
“…Insulin degradation is important in the regulation of insulin action; impairment in insulin clearance and degradation are present in various pathological conditions, including type-2 diabetes and obesity [29] . Diff erent amounts of insulin degrading activity were observed in various regions of tissues, like brain and peripheral tissues [30] . IDE can regulate 2 proteins, insulin and amyloid-β , each of which plays a central role in a common and devastating human disease.…”
Section: Discussion ▼mentioning
confidence: 99%